Existence of acute pancreatitis as a complication of dengue: a case report and literature review - Herrera, Joab A. L.; González, Brenda E. L.; Valdez, Gustavo A. H.; Moreno, Nancy G.; Camacho, Eder A. R. (International Journal of Research in Medical Sciences, 2025)
Dengue is an endemic viral infection in tropical regions, characterized by fever, myalgia, rash, and thrombocytopenia. Although most cases follow a favorable clinical course, severe complications may arise during the critical phase. Among these, acute pancreatitis is a rare but important manifestation. We present the case of a young woman with laboratory-confirmed dengue infection who, during the critical phase, developed intense and persistent abdominal pain. Laboratory tests revealed a marked elevation of pancreatic enzymes, and imaging studies confirmed the diagnosis of acute pancreatitis. She was managed conservatively with bowel rest, intravenous fluids, and analgesia, resulting in a favorable outcome without the need for invasive interventions. This case highlights the importance of considering acute pancreatitis as a potential complication in patients with dengue who present with severe abdominal pain. Early recognition and appropriate supportive treatment are essential to reduce morbidity and ensure a positive clinical outcome in such cases.